Droga ucznia niepełnosprawnego do poznania języka obcego –studium przypadku ucznia z mózgowym porażeniem dziecięcym - Bielicka, Małgorzata (Neofilolog, 2011)
The paper is a case study of a disabled student (cerebral palsy). The in-formation about the student was obtained from the interviews with him as well as his parents and teachers, school documents and a narration study which involved three psychologists. The main research questions focused on the difficulties which disabled students come across during their education. The research also addressed such issues as the role of the surroundings in the education of the disabled as well as the reasons be-hind the choice of philological studies by a disabled person.